INFORMATION AND POPULATION SERVICE SYSTEM IN SLAWI WETAN VILLAGE - Cucu Ika Agustyaningrum; Haryani; Yosep Tajul Arifin; Warjiyono (Jurnal Mantik, 2022)
Slawi Wetan Village really needs an information system that supports and provides satisfactory services for its citizens. For this reason, the author tries to make a final project on service and population information systems in Slawi Wetan Village, which until now has not been computerized. The existing system in Slawi Wetan Village is still done manually, starting from the service for covering letters of ID cards, family cards, and transfer letters to those relating to population services, population data errors, and making reports. It is possible that during the process there is an error in recording, less accurate information exists. The best solution to solving problems at the Slawi Wetan sub-district office is a computerized system. An effective and efficient activity can be achieved in supporting activities in the kelurahan. In this information system, the method used is waterfall, and in its implementation it uses the PHP programming language and MySQL as the database. Based on the results of the study, it can be concluded several things, namely: this software can be used to handle the population service process, information about the village, and knowing population data, this system can also provide print reports of village cover letters.